2020
DOI: 10.18805/lr-4401
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Biology and Reproductive Performances of Helicoverpa armigera (Hübner) Populations Across India

Abstract: Background: Helicoverpa armigera (Hübner) is an important biotic constraint to major grain legumes in India. Biological characterization of any pest species is critical for making effective management decisions. Thus, this study comprehensively presents the biological and reproductive demographic traits of different geographic populations of H. armigera across the country. Methods: In this field-laboratory investigation (2015-18), populations from 20 localities were evaluated for developmental period of all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…There are several reports which suggest that eye colour variation in insects is governed genetically (Wang et al., 2013) and diversity of pigmentation patterns in the eyes of H. armigera moths found in nature is due to an interaction between certain essential and non‐essential genes (Khan et al., 2017). Besides external phenotypic traits, morphometry of genital organs also differed significantly amongst populations, which are in accordance with earlier findings of Bashasab et al (2007) and Kranthi et al (2004), though such variations had no effect on mating success in this noctuid moth (Chakravarty et al., 2019).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…There are several reports which suggest that eye colour variation in insects is governed genetically (Wang et al., 2013) and diversity of pigmentation patterns in the eyes of H. armigera moths found in nature is due to an interaction between certain essential and non‐essential genes (Khan et al., 2017). Besides external phenotypic traits, morphometry of genital organs also differed significantly amongst populations, which are in accordance with earlier findings of Bashasab et al (2007) and Kranthi et al (2004), though such variations had no effect on mating success in this noctuid moth (Chakravarty et al., 2019).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies from our laboratory also showed that all these populations were able to freely interbreed and produce normal fertile progenies (Chakravarty et al, 2019). So the remarkable phenotypic differences amongst geographically isolated H. armigera populations of India described in the present study, seems to be due to the existence of different sub species.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Over the past decade, our working group has devoted its research efforts entirely to this particular issue. Based on the molecular characterization with RAPD markers (Deepa and Srivastava, 2011) and COI gene (Chakravarty et al, 2021), phenotyping of immature and adult stages Chakravarty et al, 2023b), and other biological traits (Chakravarty et al, 2019 and2023a), existence of sub-specific level variations among Helicoverpa armigera populations from diverse agro-ecologies of India has been deciphered. Similar studies for Leucinodes orbonalis (Padwal et al, 2022), Spodoptera litura (Ganguly et al, 2023) and Maruca vitrata (Mahalle et al, 2022) revealed genetic homogeneity for these pest species in the country.…”
Section: O N L I N E C O P Ymentioning
confidence: 99%
“…In India, it is known to attack around 96 crops, including major cereals, legumes, oilseeds, cotton, and a wide range of horticultural crops (Srivastava and Joshi, 2011). Depending on the crop, H. armigera induced damage can lead to 50 to 90% yield loss, inflicting huge monetary loss (Chakravarty et al, 2019). Correct identification of the pest is an essential requisite for devising effective IPM strategies (Chakravarty et al, 2018).…”
mentioning
confidence: 99%